Reliability Functional Model: How to Make It Applicable to the Developing Countries - Mohammad Reza Sheibani; Amir Moshari; Mehdi Zeraati (Engineering Reports)
ABSTRACT In the power systems reliability studies, all attention is generally focused on technical issues, while structural and organizational problems and weaknesses can also affect systems reliability. The problems include mismatching and overlapping duties and lack of clear responsibilities. Implementing a reliability functional model (RFM) can overcome the mentioned problems. RFM is a precise and trustworthy framework implemented to organize the reliability‐related tasks of various electricity industry entities. The NERC RFM is a practical experience carried out in the North American electricity industry. Implementation of this model in developing countries will cause problems due to insufficient infrastructure and structural differences between the electricity industry of these countries and the USA. This may lead to discouraging policymakers from executing the RFM. A modified RFM based on the conditions and structure of the electricity industry in developing countries is proposed in this manuscript. India, Turkey, Iran, and Bangladesh are considered as the case studies for the proposed model. This model is based on the NERC RFM, with necessary modifications including the elimination of some of the NERC functions, suggesting new functions, and defining new relationships between the functions.